The Wavering Power. The Portuguese hold on the Arabian coast of Oman 1622-1650 - Costa, Daniel Filipe Ferreira da (2021)
Portuguese presence in the Gulf of Oman developed, in general, since the early sixteenth century. However, the Arab shores were constantly side-lined in favour of Hormuz, the centre of Portuguese operations in the region. That changed in 1622, when the island was lost to an Anglo-Persian force. That moment, the Portuguese chose Muscat as a regional base and, as such, the Omani world became fundamental for the consolidation and enhancement of the Portuguese position as a leading power. Yet, the rule of the Omani shores proved to be difficult and hazardous. The Estado da India’s decline in resources, increasing European competition and the rise of a new united Arab entity exacerbated those difficulties and, in a few decades, Portuguese control was reduced to Muscat itself. This study addresses some of the pivotal characteristics and events related to the Portuguese presence in the Arabian coast of Oman, from the loss of Hormuz to the fall of Muscat in 1650. Therefore, military operations, commercial undertakings, financial difficulties, political decisions, religious features and tense relations are at the centre of the narrative. This way, it would be possible to understand how the Estado da India elite in Goa and the Portuguese officials in Oman acted throughout this period. Portuguese-Omani interactions started well before 1622 and continued well beyond 1650, but the three decades addressed in this dissertation can be seen as their climax.
Keywords: Relations -- Oman -- Portugal

Documents from 1548-1912 Arquivo Diplomático do Ministério dos Negócios Estrangeiros de Portugal Arquivo Distrital de Braga Arquivo Municipal de Cascais Arquivo dos Viscondes de Vila Nova de Cerveira Biblioteca da Faculdade de Direito de Lisboa Biblioteca Geral da Universidade de Coimbra Biblioteca Municipal de Elvas Colecção Pedro Pinto Museu Nacional de Arqueologia Sociedade de Geografia de Lisboa: Transcriptions, English translation, Arabic translation - Salimi, Abdulrahman al-; Jansen, Michael; Pinto, Pedro; Roy, Roopanjali; Ech-Cheikh, Mohammed; Salami, Hamid al-; Shakaili, Hilal al- (Portugal in the sea of Oman: religion and politics: research on documents, 2021)
Keywords: Relations -- Oman -- Portugal

Documents from 1611-1832 Biblioteca Nacional de Portugal (Supplement): Transcriptions, English translation, Arabic translation - Salimi, Abdulrahman al-; Jansen, Michael; Pinto, Pedro; Roy, Roopanjali; Ech-Cheikh, Mohammed; Salami, Hamid al-; Shakaili, Hilal al- (Portugal in the sea of Oman: religion and politics: research on documents, 2021)
Keywords: Relations -- Oman -- Portugal

Portugal in the Sea of Oman: religion and politics. Research on documents (Georg Olms Verlag, 2021)
Keywords: Relations -- Oman -- Portugal